Study Comparative Antioxidant Activity Scales And Tunic From Bulb Of Bawang Dayak (Eleutherine Palmifolia L Merr) - Sitti Faika Ahsan; Muhammad Wijay; Maryono Maryono (Seminar Nasional LP2M UNM, 2021)
Abstract. In literature various methods were used for extracting antioxidant compounds from Bawang Dayak (Eleutherine palmifolia L), but there is no report on optimizing the extraction of antioxidant compounds from this plant particularly in scales and tunic of bulb of Bawang Dayak. By employing ethanol with two various concentrations (50, 70%) as the solvent, dry scale leaves and tunic of Bawang Dayak (BD) were macerated for 12 to 24 h. Total phenolic content (TPC), total flavonoid content (TFC) and DPPH free radical scavenging activity of the extract were quantitatively determined. It was found that Tunic has significant highest compare with scales determined by TPC and TFC (2750.00±116.68 and 1040.35±37.52mg/100 g) values by employing 70% ethanol with maceration time 12 h. Mean while, the lowest concentration of TFC and TFC was obtained at scales when using 70% ethanol with maceration time 24 h. The result showed that highest concentration of TPC and TFC may increase scavenging activity of tunic compare with scale leaves. It is apparent that when different target (TPC, TFC, DPPH scavenging activity) is considered, different optimized extraction conditions (ethanol concentration, maceration time) may have to be used in extracting bioactive compounds for Tunic and scales of bulb of E.palmifolia. Keywords : Antioxidant, Scales, Tunic , Eleutherine palmifolia